2023
DOI: 10.3390/ani13061030
|View full text |Cite
|
Sign up to set email alerts
|

Double-Fermented Soybean Meal Totally Replaces Soybean Meal in Broiler Rations with Favorable Impact on Performance, Digestibility, Amino Acids Transporters and Meat Nutritional Value

Abstract: Inclusion of microbial fermented soybean meal in broiler feed has induced advantageous outcomes for their performance and gastrointestinal health via exhibiting probiotic effects. In this study, soybean meal (SBM) was subjected to double-stage microbial fermentation utilizing functional metabolites of fungi and bacteria. In broiler diet, DFSBM replaced SBM by 0, 25, 50 and 100%. DFSBM was reported to have higher protein content and total essential, nonessential and free amino acids (increased by 3.67%, 12.81%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The positive augmented functions of oregano, cinnamon and clove oils on growth rate and digestibility are resulted from their encapsulation by liposomes, which control the release of essential oil compounds and improve their stability ( Sherry et al, 2013 ; Cui et al, 2016 ). The mucosal barrier of the gastrointestinal tract plays a fundamental role in the absorption of nutrients, water, and electrolytes as well as shielding the gut from microbial invasion and preventing the outflow of proinflammatory molecules into the circulatory system through the gastrointestinal mucosa (Abdel-Raheem et al, 2023) . The TJP regulated the mucosal barrier of the gastrointestinal tract and they consisted of several unique proteins including occludin, JAM-2, zona occludens-1, and claudins-1, which are fundamental for making an intact physical barrier between the gut epithelial cells ( Pham et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The positive augmented functions of oregano, cinnamon and clove oils on growth rate and digestibility are resulted from their encapsulation by liposomes, which control the release of essential oil compounds and improve their stability ( Sherry et al, 2013 ; Cui et al, 2016 ). The mucosal barrier of the gastrointestinal tract plays a fundamental role in the absorption of nutrients, water, and electrolytes as well as shielding the gut from microbial invasion and preventing the outflow of proinflammatory molecules into the circulatory system through the gastrointestinal mucosa (Abdel-Raheem et al, 2023) . The TJP regulated the mucosal barrier of the gastrointestinal tract and they consisted of several unique proteins including occludin, JAM-2, zona occludens-1, and claudins-1, which are fundamental for making an intact physical barrier between the gut epithelial cells ( Pham et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Muniyappan et al (2023) concluded that growth performance, apparent total digestibility and blood status of weaned piglets were improved after replacing soybean meal with fermented soybean meal. Similarly, Abdel-Raheem et al (2023) found that fermented soybean meal in broiler diets has a positive impact on feed utilisation of broilers, promotes amino acid transport and improves the nutritional value of brisket. Moreover, soybean meal fermented by microbes has a specific aroma, which can increase the appetite of animals and reduce feed waste (Sari et al, 2018).…”
Section: Application Of Fermented Soybean Mealmentioning
confidence: 96%
“…Similarly, Abdel‐Raheem et al . (2023) found that fermented soybean meal in broiler diets has a positive impact on feed utilisation of broilers, promotes amino acid transport and improves the nutritional value of brisket. Moreover, soybean meal fermented by microbes has a specific aroma, which can increase the appetite of animals and reduce feed waste (Sari et al ., 2018).…”
Section: Application Of Fermented Soybean Mealmentioning
confidence: 99%
“…Fermentation is a dynamic process aiming to break down complex molecules in feed into small simpler ones using microorganisms, substrates and environmental conditions [8]. Furthermore, fermentation can enhance the nutritional properties of feed ingredients [9,10] reducing the toxic elements and various antinutritional factors [11]. Fermentation technology using probiotic bacteria can enhance the concentration of probiotics, enzymes, organic acids, bioactive peptides and metabolites and may alter some compounds into more valuable components in fermented ingredients [12].…”
Section: Introductionmentioning
confidence: 99%